Network pharmacology and experimental verification of the potential mechanism of Er-Xian decoction in aplastic anemia - Mei Ye; Guangxian Liu; Yujun Yang; Hongyu Yang; Juan Ren; Wenfei Chen; Zeli Gao (Scientific Reports, 2023)
Abstract To investigate the potential mechanism of Er-Xian decoction (EXD) in treating aplastic anemia (AA), the active components of EXD were screened by the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP), and the targets of the components were predicted by the Swiss Target Prediction database. AA targets were collected from the GeneCards, OMIM, DisGeNET, PharmGKB, DrugBank, and TTD databases, the intersection of AA targets and EXD targets was calculated, and an herb-component-target network was constructed by Cytoscape 3.7.2 software. The STRING database was used for protein‒protein interaction (PPI) analysis, and Cytoscape 3.7.2 software was used to construct a PPI network and perform topology analysis. The core targets were imported into the DAVID database for gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. The molecular docking software AutoDock was used to measure the affinity between active components and key targets. Finally, we established a mouse model of AA and verified the key targets and signaling pathways of EXD by RT‒PCR, ELISA and Western blot analysis. A total of 53 active components were screened from EXD, 2516 AA-related targets were collected, and 195 common targets were obtained. An herb-component-target network and a PPI network were successfully constructed, and 36 core targets were selected from the PPI network. The main active components of EXD include luteolin, kaempferol, berberine, etc., and key targets include PIK3CA, AKT1, STAT3, etc. GO functional enrichment analysis showed that cell components, molecular functions and biological processes with significant correlations were macromolecular complexes, protein serine/threonine/tyrosine kinase activity and protein phosphorylation, respectively. KEGG pathway analysis showed that the pathways with significant correlations included the PI3K-Akt signaling pathway and JAK-STAT signaling pathway. Molecular docking results showed that the tested key targets had good affinity for the corresponding active components. In AA mice, we found that EXD significantly increased white blood cell count, red blood cell count, platelet count and hemoglobin levels, increased mRNA levels of PIK3CA, PIK3CD, AKT1, JAK2, STAT3 and MAPK1, and promoted phosphorylation of PI3K, AKT, ERK1/2 and STAT3. In summary, EXD acts on PI3K, AKT, STAT3 and other targets through berberine, luteolin, quercetin and other components to regulate the PI3K-Akt pathway, JAK-STAT pathway and other pathways, thus exerting its therapeutic effect on AA. This study explained the Chinese medicine theory of treating AA with EXD by tonifying kidney-yang and provides a scientific basis for the use of EXD in treating AA.